EXPLORING AN ONLINE LANGUAGE TEACHING TASK DESIGN AND ITS IMPLEMENTATION: A CASE STUDY IN AN ONLINE COURSE - Romadhon Romadhon; Pupung Purnawarman; Didi Sukyadi (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
During the outbreak issues, English online courses become an alternative for students to deepen and strengthen their English proficiency. Task-based language teaching (TBLT) in an online environment requires a framework that teachers or developers follow. As in schools, online courses also have a task design to guide teaching and learning. Hence, it is essential to investigate an online language task design and also its implementions whether based on any framework or not. This study conducted a qualitative case study design focusing on a newly established English online course as the main resource for collecting detailed and in-depth data. Since it was recently established, it has provided relevant data on how a task design was developed. Therefore, this study explores a task design in a recently established online course using Hampel's an online language teaching framework (2006), consisting of three levels: approach, design, and procedure. Data collections were taken from an open-ended questionnaire of all tutors using a google form, document analysis of the syllabus of the beginner class level, and classroom observation from recorded videos of the learning process. Those data were analyzed using Hampel’s framework to present approach, design, and procedure the online course embodied. The findings show that the online course followed the Hampel's online language teaching framework from the task design to implementations. Even though implicitly implemented, the online course incorporated second language acquisition, sociocultural and medium, mode, and affordance. Its design and procedure only consisted of the content's organization and objectives without further information about instructional teaching and medium, modes, and affordance. This study is appropriate as a recommendation for online English language teaching provided by online courses or formal schools to rethink their task design.